Rainfall Characteristics Analysis of Kutch (Gujarat) Region of India - Singh, R S; Ramakrishna, Y S; Purohit, R S (Annals of Arid Zone, 2016)
The rainfall characteristics analysis of Kutch district (Gujarat), India based on the rainfall data of 12stations for the period 1901 to 1989 revealed that the rainfall has decreasing trend from SW region to NE region. Probability of weekly rainfall distribution worked out by ranking order method revealed that interior part of the district is more prone to drought conditions as compared to coastal plains. Most of the stations had recorded highest observed rainfall values nearer to the estimated rainfall of 100 years return period except at Bhuj, Anjar and Rahapur.